Common ownership and the (non-)transparency of institutional shareholdings: An EU-US comparison - Sebastian Steuer (Leibniz Institute for Financial Research SAFE, 2022)
This paper compares the extent of common ownership in the US and the EU stock markets, with a particular focus on differences in the applicable ownership transparency requirements. Most empirical research on common ownership to date has focused on US issuers, largely relying on ownership data obtained from institutional investors' 13F filings. This type of data is generally not available for EU issuers. Absent 13F filings, researchers have to use ownership records sourced from mutual funds' periodic reports and blockholder disclosures. Constructing a 'reduced dataset' that seeks to capture only ownership information available for both EU and US issuers, I demonstrate that the 'extra' ownership information introduced by 13F filings is substantial. However, even when taking differences in the transparency situation into due account, common ownership among listed EU firms is much less pronounced than among listed US firms by any measure. This is true even if the analysis is limited to non-controlled firms.
Keywords: G23; G34; G38; K22; L10; L41; 330; common ownership; profit weights; ownership disclosure; 13Ffilings; index funds; passive investors; institutional investors; Big Three